A COMPARATIVE STUDY OF LIPID PROFILE AND ANTIOXIDENTS BETWEEN INDIANS AND IRANIANS IN MYSORE,INDIA - Pourmolaei, Shokoufeh; Ashkavand, Zahra; CLETUS J.M.D’SOUZA, (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: High Density Lipoprotein (HDL) particles are distinguished by their capacity to exert a wide spectrum of antiatherogenic biological activities, including their ability to protect Low Density Lipoprotein (LDL) against oxidation, and their potent anti-inflammatory actions on cells of the arterial wall. Since now cardiovascular disease ( CVD) is beginning to be recognised as a consequence of inflammation, attention is focussed not only on oxidation but also on inflammation which may be measured as circulating levels of an acute-phase protein, such as C-reactive protein (CRP). Methods: 5ml of blood was drawn from subjects (Iranians and Indians) in fasting. Lipid profile and lipid per -oxidation and anti-oxidant activities were measured. Results: our result showed that the serum lipoproteins of Indians readily get oxidized by Cu++ or benzoyl peroxide. Interestingly, the serum lipoprotein of Iranians living in Mysore also showed a similar profile of Cu++ and Benzoyl peroxide catalysed oxidation. Conclusion: Life style and classical risk factors yet higher HDL and higher Paraoxonase (PON) activity in the blood of the Iranians suggests that diet can make a different to the conventional risk factors. Keywords: Lipid profile, CVD, Inflammation, PON,CRP